Analisis Pengaruh Physical Evidence, Price, Service, Location Dan Salesperson Terhadap Buying Intention Di Spazio Office Building - Hartanto, Cynthia Christina (Jurnal Strategi Pemasaran, 2014)
Developments property bussiness in Surabaya has grown rapidly both price and volume of sales that cause property business competition is getting tight. Knowing what are the preferences of consumers buying intention is essential for companies to be able to sharpen their competitiveness in order to increase product sales. In this case, the researcher intends to use the title